Tabersonine enhances cisplatin sensitivity by modulating Aurora kinase A and suppressing epithelial–mesenchymal transition in triple-negative breast cancer - Xi Chen; Yuanliang Yan; Yuanhong Liu; Qiaoli Yi; Zhijie Xu (Pharmaceutical Biology)
Context Tabersonine has been investigated for its role in modulating inflammation-associated pathways in various diseases. However, its regulatory effects on triple-negative breast cancer (TNBC) have not yet been fully elucidated.Objective This study uncovers the anticancer properties of tabersonine in TNBC cells, elucidating its role in enhancing chemosensitivity to cisplatin (CDDP).Materials and methods After tabersonine (10 μM) and/or CDDP (10 μM) treatment for 48 h in BT549 and MDA-MB-231 cells, cell proliferation was evaluated using the cell counting kit-8 and colony formation assays. Quantitative proteomics, online prediction tools and molecular docking analyses were used to identify potential downstream targets of tabersonine. Transwell and wound-healing assays and Western blot analysis were used to assess epithelial–mesenchymal transition (EMT) phenotypes.Results Tabersonine demonstrated inhibitory effects on TNBC cells, with IC50 values at 48 h being 18.1 μM for BT549 and 27.0 μM for MDA-MB-231. The combined treatment of CDDP and tabersonine synergistically suppressed cell proliferation in BT549 and MDA-MB-231 cells. Enrichment analysis revealed that the proteins differentially regulated by tabersonine were involved in EMT-related signalling pathways. This combination treatment also effectively restricted EMT-related phenotypes. Through the integration of online target prediction and proteomic analysis, Aurora kinase A (AURKA) was identified as a potential downstream target of tabersonine. AURKA expression was reduced in TNBC cells post-treatment with tabersonine.Discussion and conclusions Tabersonine significantly enhances the chemosensitivity of CDDP in TNBC cells, underscoring its potential as a promising therapeutic agent for TNBC treatment.